2018
DOI: 10.3390/pr6120246
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification For Continuous Fluidized Bed Spray Agglomeration

Abstract: Agglomeration represents an important particle formation process used in many industries. One particularly attractive process setup is continuous fluidized bed spray agglomeration, which features good mixing as well as high heat and mass transfer on the one hand and constant product throughput with constant quality as well as high flow rates compared to batch mode on the other hand. Particle properties such as agglomerate size or porosity significantly affect overall product properties such as re-hydration beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…They demonstrated that the combination of DYS and shear-cell simulations is beneficial, using data from their experimental system for validation. Golovin et al [7] proposed a population balance model for a continuous fluidized bed spray agglomeration and validated it using experimental data. The main focus was on the description of the dynamic behavior in continuous operation mode in a certain neighborhood around steady-state.…”
Section: Parameter Estimation/model Calibrationmentioning
confidence: 99%
“…They demonstrated that the combination of DYS and shear-cell simulations is beneficial, using data from their experimental system for validation. Golovin et al [7] proposed a population balance model for a continuous fluidized bed spray agglomeration and validated it using experimental data. The main focus was on the description of the dynamic behavior in continuous operation mode in a certain neighborhood around steady-state.…”
Section: Parameter Estimation/model Calibrationmentioning
confidence: 99%
“…(I) In the top-down-modeling approach, only a few particle properties are taken into account (often only one). The unknown fluxes and source/sink mechanics of the corresponding PBEs are either described by semi-empirical approaches or adapted to experimental data with suitable methods (see, e.g., [61][62][63][64][65][66]). (II) In contrast, the bottom-up approach is based on detailed first-principle modeling of the individual particle behavior, e.g., ordinary or stochastic differential equations, which is adapted to single-particle experimental data.…”
Section: Population Balance Modelingmentioning
confidence: 99%
“…The most widely used and successful method for the analysis and quantitative prediction of the granulation processes is the approach based on population balance modeling [19][20][21][22][23]. The population balance equation (PBE), which is based on the law of conservation of mass, is a mathematical description of how the particle size distribution evolves [24].…”
Section: Introductionmentioning
confidence: 99%